Syzygium cumini na glicemia, estresse oxidativo e sistema colinérgico de ratos normais e diabéticos - Andrade, Cinthia Melazzo de (2002)
The objective of the present work was to investigate the efficiency of the bark extract of Syzygium cumini (L.) Skeels, a plant commonly used in the alternative medicine treatment for diabetes, evaluating its therapeutic effect on glycemic levels, oxidative stress and cholinergic system of normal and alloxan induced diabetic rats. The animals were divided in control group (C), control treated group (CT), diabetic control group (DC) and diabetic treated group (DT). In a first experiment the oral administration of aqueous extract of Syzygium cumini bark, on the dose of 1g/kg daily for thirty days didn't result in a significant reduction on the blood glucose and glycosilated hemoglobin levels. The treatment with Syzygium cumini extract caused a significant (p<0.05) increase on the levels of substances reactive to thiobarbituric acid (TBA-RS) on the plasma of the DT group when compared to the C group. The catalase activity in the kidney of the DC group diminished significantly (p<0.01), and in the liver there was a significant (p<0.01) increase of this enzyme in the same group. These results indicate that the Syzygium cumini bark extract does not possess an anti-hyperglycemic effect on alloxan induced diabetic rats. The antioxidant effect of the plant extract was not sufficient to reduce the TBA-RS production. The reduction of the catalase activity in the kidneys may be due to its exhaustion or inhibition and its increase in the liver was due to the oxidative stress caused by the diabetic state. In a second experiment the effect of the Syzygium cumini bark extract on the cholinergic system of normal and diabetic rats was evaluated. The acetylcholinesterase (AChE) activity was determined in the following structures: cerebellum, cortex, striatum and hippocampus. A diminution was observed in the AChE activity of the cerebellum and cerebral cortex in the DT group (p<0.05). In the striatum there was an increase of the enzyme activity in the CT group (p<0.05). The hippocampus showed no significant variation. The extract therapy demonstrated its inhibitory effect of the AChE on the cerebellum and cerebral cortex, and an increase of the enzyme in the striatum, indicating a possible functional alteration of the central nervous system.